THE DIRECTOR'S ROLE IN THE SHORT FILM ‘KEEPING ADAB’ - Tuty Mutiah; Andi Setyawan; Chepi Nurdiansyah; Fitriyanto (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This research aims to examine the role of the director in the process of making a short film entitled Menjaga Adab. The director has an important function in transforming the vision of the story into an effective visual representation and conveying a moral message about the importance of maintaining manners in everyday life. The approach used in this research is a qualitative method by conducting direct observation during the production process, interviews with the director, and analysis of the film content. The research findings reveal that the director is not only responsible for the shooting and direction of the actors, but also maintaining the consistency of the adab values to be conveyed through each scene and dialogue. In conclusion, the success of the short film Menjaga Adab is highly dependent on the director's ability to combine social and ethical messages in harmony with the technical and artistic aspects of the film. This research provides insight into the importance of the director's role as the main driver in the production of films that focus on social values education